Task-based language teaching in academic English higher education: a case of low-proficiency learners in Thailand - Budi Waluyo,; Thinley Wangdi, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Amid the rising interest in task-based language teaching (TBLT) adoption within higher education, scant attention has been paid to its implications for students with low English proficiency who are enrolled in academic English courses. Therefore, employing a mixed-method research design, this study implemented and assessed the impact of TBLT in an academic English curriculum, with a specific focus on speaking skills, over a 12-week duration. The research involved 205 first-year university students in Thailand, representing diverse academic disciplines (22% male, 78% female). Quantitative data encompassed in-class TBLT participation scores, final speaking test results, and course grades, while qualitative insights were drawn from reflective essays. The quantitative data underwent both descriptive and inferential statistical analysis, whereas thematic analysis was applied to the qualitative data. The quantitative analysis disclosed noteworthy outcomes: 1) a moderate level of engagement among low-proficiency participants; 2) a robust correlation between classroom engagement, communicative proficiency, and academic performance, with engagement emerging as a significant predictor; and 3) superior progress among highly and moderately engaged students compared to their less-engaged peers. Qualitative analysis unveiled four pivotal themes, aligning with prevailing language acquisition theories, highlighting the pivotal role of speaking exercises in enhancing fluency and self-assurance, promoting active learner involvement, fostering an enriching learning environment, and enhancing language applicability to real-world contexts. In summation, these findings advocate for augmented incorporation of speaking exercises in language pedagogy, emphasising the interconnected dimensions of linguistic, cognitive, emotional, and social facets within the language learning journey.